The invasive potential of parasitic monogenoids (platyhelminthes) via the aquarium fish trade: an appraisal with special reference to India. (16th May 2013) - Tripathi, Amit
Abstract Aquaculture, the rearing of aquatic organisms under controlled or semi‐controlled conditions to produce organisms, mainly for food, ornamental and sporting purposes, is a fastest‐growing animal‐food‐producing sector in the world. The human‐mediated introduction of exotic fish has played an important role in the success story of aquaculture. Nonetheless, many exotic fish have been implicated in the loss of native fish biodiversity, largely through the transmission of parasites and diseases amongst others. Whilst the transmission of parasites following the introduction of exotic food fish is well documented, transfer of those carried by exotic ornamental fish has received little attention. This article provides the first summary review of the global translocation of the platyhelminthes class Monogenoidea via the aquarium fish trade to draw attention to the growing parasitological risk factors associated with this form of commerce. By examining the invasive characteristics of both aquarium fish and monogenoids, I review how the monogenoids fit into the different stages that an introduced species goes through when invading the destination environment. For this, I use a theoretical framework, synthesising published reports on the aquarium fish trade with current knowledge on monogenoids to model invasion success. Next, I provide examples of invasive monogenoids on exotic Indian aquarium fish and briefly discuss the vulnerability of India to colonisation by imported aquarium fish and their parasitic monogenoids. I conclude that the aquarium fish trade is a perfect gateway for worldwide translocation of monogenoids. As this trade continues to increase and intensify, global translocation of monogenoids will expand even further.